Cirrhotic Endothelial Progenitor Cells Enhance Liver Angiogenesis and Fibrosis and Aggravate Portal Hypertension in Bile Duct-Ligated Cirrhotic Rats - Tripathi, Dinesh Mani; Hassan, Mohsin; Siddiqui, Hamda; Kaur, Impreet; Rawal, Preety; Bihari, Chaggan; Kaur, Savneet; Sarin, Shiv K. (Frontiers in Physiology, 2020)
Background: Circulating cirrhotic endothelial progenitor cells (EPC) interact with both liver sinusoidal endothelial cells (LSEC) and hepatic stellate cells (HSC) and promote angiogenesis in vitro. In the current study, we evaluated the in vivo effects of EPCs on LSECs and HSCs in rat models of liver cirrhosis. The current study evaluated the effect of cirrhotic and control EPCs on hepatic angiogenesis, microcirculation and fibrosis in vivo. Methodology: Cirrhotic animal models were prepared by identifying and ligating the bile duct (BDL). Circulating EPCs isolated from healthy human and cirrhotic blood were characterized by flow cytometry, cultured ex vivo and transplanted in different groups of BDL rats via tail vein two weeks after the ligation. The cells were given thrice a week for two weeks. The untreated group of BDL rats received only saline. Fibrosis was evaluated by masson’s trichrome staining. Dedifferentiated LSECs were identified by expression of CD31 and activated HSCs were marked as alpha-SMA-positive cells and were studied by immunohistochemistry and western blotting in saline-, healthy EPC- and cirrhotic EPC-treated rats. In vivo, hepatic and systemic hemodynamic parameters were evaluated. Liver functions were evaluated. Results: Fibrosis studies revealed an increase of fibrosis (from grade 2 to 4) in cirrhotic EPC-treated rats as compared to healthy EPC-treated and saline-treated rats. Immunohistochemical and western blot data showed an enhancement of both fibrosis and angiogenesis markers, alpha-SMA and CD31 in cirrhotic EPC-treated rats as compared to healthy EPC-treated and saline-treated rats (P<0.01 for each). Cirrhotic EPC-treated BDL rats had high portal pressure and portal blood flow with significantly increased hepatic vascular resistance in comparison to healthy EPC- and saline-treated BDL animals, without significant differences in mean arterial pressure. Cirrhotic EPC-treated BDL rats also showed a substantial increase in the hepatic expression of angiogenic receptors, VEGFR2 and CXCR4 in comparison to saline-treated rats. Conclusion: The study suggests that transplantation of cirrhotic EPCs enhance LSEC differentiation and angiogenesis, activate HSCs and worsen fibrosis, thus resulting in hepatic hemodynamic derangements in BDL-induced cirrhosis.